PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI DAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (Studi Pada Kantor Badan Kepegawaian Daerah Provinsi Jawa Tengah) - Sarido, Sarido; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2016)
In achieving the objectives of the organization, of course, must take into consideration several factors that influence performance. Among them is communication, compensation, organizational commitment and motivation. The purpose of this study was to analyze the influence of communication on motivation, compensation effect on motivation, communication influence on organizational commitment, influence of compensation on organizational commitment, communication influence on the performance, the effect of compensation to performance, the effect of motivation on the performance and influence of organizational commitment to performance. The population in this study were employees of the Regional Employment Board Central Java Province some 167 people. Methods of data collection using purposive sampling method in which sampling based on predetermined criteria. Data processing was performed using SPSS 19.0. The analysis used in this research are descriptive statistics, test instruments and multiple linear regression. Conclusions from the study indicate that communication has a positive and significant impact on the motivation, compensation has a positive and significant impact on the motivation, communication has a positive and significant impact on organizational commitment, compensation has a positive and significant impact on organizational commitment, communication has a positive and significant impact on the performance, compensation has a positive and significant impact on performance, motivation has a positive and significant impact on performance, organizational commitment has a positive and significant impact on performance. Keywords : communication, compensation, motivation, organizational commitment and performance.